2020
DOI: 10.29252/nfsr.7.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aloe Vera and Swimming Training on Lipid Profile of Streptozotocin Induced Diabetic Rats

Abstract: Background and Objectives: Exercise and nutrition are two effective factors in controlling diabetes-induced metabolic disorders. The aim of this study was to assess effects of aloe vera and swimming training on lipid profile of the diabetic rats. Materials and Methods: In this experimental study, 72 diabetic rats were selected and divided into nine groups of eight rats, including 1) four weeks of aloe vera consumption (FAV), 2) six weeks of aloe vera consumption (SAV), 3) four weeks of swimming (FS), 4) six we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…In an experimental study on streptozotocin‐induced diabetic rats, the hypolipidemic effects of AVG were evaluated. The findings of this study demonstrated that consumption of AVG for 6 weeks significantly decreased levels of TG, TC, LDL, and very‐low‐density lipoprotein cholesterol (VLDL) (Hosseini et al, 2020). Furthermore, AVG treatment at doses of 100 and 200 mg/kg/day showed beneficial effects against dyslipidemia and oxidative stress; also, prevented the accumulation of adipose tissue in obese rats (Rahoui et al, 2018).…”
Section: Pharmacological Effectsmentioning
confidence: 73%
“…In an experimental study on streptozotocin‐induced diabetic rats, the hypolipidemic effects of AVG were evaluated. The findings of this study demonstrated that consumption of AVG for 6 weeks significantly decreased levels of TG, TC, LDL, and very‐low‐density lipoprotein cholesterol (VLDL) (Hosseini et al, 2020). Furthermore, AVG treatment at doses of 100 and 200 mg/kg/day showed beneficial effects against dyslipidemia and oxidative stress; also, prevented the accumulation of adipose tissue in obese rats (Rahoui et al, 2018).…”
Section: Pharmacological Effectsmentioning
confidence: 73%
“…Bellamy et al (2006) reported that the induction of diabetes by STZ for eight weeks in rats caused cellular damage or cell loss in the cerebellum (13). Lechuga Sancho et al also showed that in diabetes, the activity of Caspase-3 cells continuously increases in all layers of the cerebellum, causing destruction, degeneration, and cellular changes in both glial (astrocyte, microglia) and purkinje cells, while the two above-mentioned cell groups form a common unit for the transmission of the synaptic information (26). During the diabetes period, the glucose consumption in the brain decreases, which causes the brain to become increasingly a vulnerable tissue (27).…”
Section: Discussionmentioning
confidence: 99%